FANOMICS® Turn Customers into Fans and Profit from it - Becker, Roman; Daschmann, Gregor (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2023)
Every company wants to turn its customers into true and lifelong fans. In this book, Roman Becker and Gregor Daschmann, the discoverers of the Fan Principle and FANOMICS, demonstrate how this can be actually accomplished. They transfer the mechanisms of fan relationships from sports, music, and art to those between companies and customers. What turns a customer into a "fan" customer? How are these identified? And how can the Fan Rate be managed and even increased? This book provides answers to all these questions. Based on surveys and interviews with more than 100,000 respondents, it becomes clear that fans have the highest customer value and therefore contribute significantly to the economic success of a company. However, in order to win fan customers and increase these numbers, a complete rethinking of customer relationship management and a departure from the customary key performance indicators is necessary. Taking this path is extremely worthwhile. Fan customers have an emotional connection to their provider and form a new, reliable "currency" - both as direct buyers and as active ambassadors. This a must-read for all business decision-makers who want to improve the quality of their customer relationships, while saving money and achieving more than just short-term success. From the contents: - Definition of fan customers and what "emotional customer loyalty" means - Distinct value of the fan customer as a value-added partner and ambassador - FANOMICS as a management program in customer relationship management - Concrete suggestions for implementing the FANOMICS - Best practices and illustrative examples of tops and flops from the business world Visit the website www.fanomics.de for more information.
Chapter 1 The Fan Principle: Fans and Fan Customers -- 1.1 What it is about -- 1.2 What is a fan? -- 1.3 From Fan Principle to FANOMICS: What is a Fan Customer? -- 1.4 The FANOMICS Basis: The Fan Indicator -- 1.5 The Fan Rate as a KPI -- 1.6 The Fan Portfolio -- 1.7 Bibliography -- Chapter 2 The value of fan customers -- 2.1 The fan as a growth driver -- 2.2 Fans and Market Penetration: Growth with existing customers in existing business -- 2.3 Fans and Market development: Growth through the acquisition of new customers in existing business -- 2.4 Fans and product development: Growth with existing customers through expansion of the product range -- 2.5 Fans and product diversification: Growth by attracting new customers for new products -- 2.6 Summary: The Fan Rate as the central growth factor -- 2.7 Increasing customer value through FANOMICS -- 2.8 Bibliography -- Chapter 3 FANOMICS - The Economics of the Fan Principle -- 3.1 Focus generates identification -- 3.2 Orchestration creates perceived uniqueness -- 3.3 Definition of FANOMICS -- 3.4 Example VI: ALDI South - the simple principle -- 3.5 Examples VII: Miele - Orchestration of performance and communication -- 3.6 FANOMICS: From development to implementation -- 3.7 Bibliography -- Chapter 4 How do I really turn customers into fans? -- 4.1 Positioning -- 4.2 Orchestration -- 4.3 Employees as Fan Makers -- 4.4 Customer value-based control -- 4.5 Bibliography -- Chapter 5 FANOMICS: More than controlling relationship quality -- 5.1 Customer value-based segmentation with the Fan Portfolio -- 5.2 FANOMICS as an instrument for efficient new customer acquisition -- 5.3 Dovetailing of NPS and FANOMICS to form "NPSplus Insights" -- 5.4 Bibliography -- Chapter 6 Success Factors of FANOMICS -- 6.1 Building awareness and acceptance -- 6.2 Validation of success effectiveness by measuring the customer value of Fans -- 6.3 Continuous measurement and goal systems for managing success -- 6.4 Bibliography. .
Keywords: Marketing; Sales management; Management; Marketing; Sales and Distribution; Management